IMPLEMENTASI MODEL PEMBELAJARAN KEMANDIRIAN BERBASIS SATYA DAN DARMA PRAMUKA DALAM MEMBENTUK GENERASI MUDA MANDIRI PADA KEGIATAN ALAM TERBUKA - Utang Mochamad Muchtar; Sutaryat Trisnamansyah (JIV-Jurnal Ilmiah Visi, 2011)
The aims of out of school education is to make independent human, especially the young generation. Now, many problems which found in young generations, like juvenile delinquency, drugs, rape, and the otehers problem which impacts of the weakness nationâ€™s potential, so it must be done. Scouting method is a solution which expacted to give education value to make indpendent young generation. This sarticle specially discuss abaout implementation indepence learning model based Satya and Darmaâ€™s Scout to make independent young generation in open natural activity. This article conclude that effectiveness of independence learning model in open natural activity if implemented according to scoutâ€™s fundamental principles and method by a deeper understanding the meaning of the life in universe.